A looking-out portal (LOP) approach to enhance qualitative aspects of bandwidth utilisation in academic networks. (1st January 2011) - Ahmed, Waseem; Ansari, Zahid; Herrmann, Johannes; Abdullah, Matin
Campuses of educational institutions periodically need to increase network bandwidth to keep up with increased demand and this decision is based on the quantitative aspects of the network bandwidth utilisation. The qualitative utilisation of the bandwidth is seldom looked into. Improving the qualitative utilisation of the bandwidth may not even necessitate a network upgrade. Although blacklist-based access control techniques help to a certain degree, the findings of this research indicate otherwise. A multi-tier, whitelist-based, looking-out portal (LOP) approach is presented that promises to improve the qualitative utilisation of the network while positively impacting pertinent resource identification and location of sources on the internet. The authors draw on their years of experience serving as students and staff in various campuses of universities and colleges in various countries while making recommendations.